Overlapping Regional Regulations on Subak in Bali and Their Conflict with National Law - Abitha Satria, I Gede; Yusa, I Gede; Gede Astariyani, Ni Luh (Westscience Press, 2025)
Subak is a traditional Balinese agrarian system recognized by UNESCO as a World Cultural Heritage. However, its sustainability faces serious threats due to regulatory overlaps between regional and national legislation, particularly regarding the protection of agricultural land. This study aims to examine the normative conflict between regional regulations in Bali and Law Number 41 of 2009 on the Protection of Sustainable Agricultural Land. Using a normative juridical method and statutory approach, the research reveals substantial differences in the regulation of Subak land use. Several regional bylaws permit the conversion of agricultural land for development purposes, which contradicts national legal norms that emphasize the preservation of sustainable agriculture. The study recommends regulatory harmonization and policy revision at the regional level to align with the goals of Subak protection and national food sovereignty.